2015
DOI: 10.1007/s10482-015-0530-3
|View full text |Cite
|
Sign up to set email alerts
|

Verrucomicrobial community structure and abundance as indicators for changes in chemical factors linked to soil fertility

Abstract: Here we show that verrucomicrobial community structure and abundance are extremely sensitive to changes in chemical factors linked to soil fertility. Terminal restriction fragment length polymorphism fingerprint and real-time quantitative PCR assay were used to analyze changes in verrucomicrobial communities associated with contrasting soil nutrient conditions in tropical regions. In case study Model I (“Slash-and-burn deforestation”) the verrucomicrobial community structures revealed disparate patterns in nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 54 publications
(82 reference statements)
7
43
1
3
Order By: Relevance
“…Nevertheless, other researchers have come to different conclusions based on similar results. Navarrete et al [56], for instance, correlated an increase in Verrucomicrobia with low soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other researchers have come to different conclusions based on similar results. Navarrete et al [56], for instance, correlated an increase in Verrucomicrobia with low soil fertility.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies have shown that individuals within the phylum Verrucomicrobia often benefit and become more abundant in areas that lack a straw covering. Members of this phylum have been described as highly selective for areas of low soil fertility and poor soil quality (Navarrete et al ., ). It is therefore likely that this taxonomic group might be effectively used to monitor the biological depletion of soil quality in sugarcane fields.…”
Section: Impacts Of Straw Removal On Soil Biological Attributesmentioning
confidence: 97%
“…() observed that straw removal modified the fungal communities present in soil, but did not affect bacterial communities. However, other studies have shown that microbial communities can be shaped by straw management as well as through the addition of organic or mineral fertilizers (Rachid et al ., ; Navarrete et al ., ; Pitombo et al ., ). All these studies have shown that individuals within the phylum Verrucomicrobia often benefit and become more abundant in areas that lack a straw covering.…”
Section: Impacts Of Straw Removal On Soil Biological Attributesmentioning
confidence: 97%
“…Indeed, while a recent study suggested that members of this phylum favour higher moisture soils (Maestre et al, 2015), another study noted that their abundance increased following droughts and heat waves (Acosta-Martinez et al, 2014) and Buckley et al (2001) suggest that they are negatively associated with moisture. As with the Acidobacteria, the ecology of soil Verrucomicrobia is poorly understood; however, evidence for their abundance in soil is increasing, in particular, in grassland biomes (Buckley & Schmidt, 2001;Bergmann et al, 2011;Fierer et al, 2013;Carbonetto et al, 2014;Navarrete et al, 2015). This study provides further support for the Verrucomicrobia dominance of soil microbial communities and suggests that members of this phylum and, more specifically, the class Spartobacteria show variability in their response to moisture, even within a single habitat, suggesting that they may have a diverse functional role in soil.…”
Section: Class Order Familymentioning
confidence: 99%